A New DCT Based Watermarking Method Using Luminance Component - Yesilyurt, M.; Yalman, Y.; Ozcerit, A. T. (Elektronika ir Elektrotechnika, 2013)
The main purpose of the digital watermarking isto provide information security and copyright protection. Fromthis point of view, a robust blind watermarking method basedon Discrete Cosine Transform for colour images is proposed inthis paper. The proposed method provides hiding a binarywatermark in a compressed Digital Colour Image. First, theDigital Color Image is transformed into YCbCr from RGBcolor space and then the Discrete Cosine Transform middleband of the luminance (Y) component is used for watermarkingprocesses. Each bit of the binary watermark is embedded in adifferent Discrete Cosine Transform block. Thus, deteriorationon the image is minimized achieving high invisibility. Thesituation is checked whether the watermark is lost after theimage saved. If the watermark is lost in any block, the averageof some neighbouring Discrete Cosine Transform coefficients isused for embedding the watermark bit. The experimentalresults show that the proposed method can be safely used whenpoint of interest is binary watermarks. Moreover, extractionprocesses do not need the cover image and the watermark isrecovered completely. Statistical and perceptual qualityevaluations show that the proposed method is better than itscounterparts. DOI: http://dx.doi.org/10.5755/j01.eee.19.4.2015